COMPOSITIONAL VARIATION OF PYROXENE AND MICA FROM THE LITTLE MURUN ULTRAPOTASSIC COMPLEX, ALDAN SHIELD, RUSSIA - Mitchell R.H.; Vladykin N.V. (My University, 1996)
Pyroxene and mica found in plutonic rocks of the Little Murun ultrapotassic pluton exhibit trends of compositional evolution that permit evaluation of the differentiation sequence of the complex. Pyroxene evolves from diopside in kalsilite and phlogopite pyroxenites through aegirine-diopside in shonkinite to aegirine in late stage charoitite and evolved hypabyssal rocks. The compositional trend is unusual in that the hedenbergite content of the pyroxenes never exceeds 15 mol.% and is thus unlike pyroxene compositional trends found in sodic alkaline complexes. Mica is A1-and Ti-poor and ranges in composition from Fe-rich phlogopite through biotite towards tetraferriannite. Compositional trends of mica found in 'lamproite-like' hypabyssal rocks are identical to those observed in the micaceous plutonic rocks; hence the former are considered to be representatives of the lamprophyric facies of the magmas which formed the plutonic series.